Preparation and evaluation of charged solid lipid nanoparticles of tetrandrine for ocular drug delivery system: pharmacokinetics, cytotoxicity and cellular uptake studies. (July 2014) - Li, Jiawei; Guo, Xiujun; Liu, Zhidong; Okeke, Chukwunweike Ikechukwu; Li, Nan; Zhao, Hainan; Aggrey, Mike Okweesi; Pan, Weisan; Wu, Tao
Abstract In this study, tetrandrine-loaded cationic solid lipid nanoparticles (TET-CNP) and solid lipid nanoparticles (TET-NP) were prepared by the emulsion evaporation-solidification at low temperature method. The particle size, zeta potential, and entrapment efficiency of TET-CNP and TET-NP were characterized. The results showed that the TET-CNP and TET-NP had average diameters of (15.29 ± 1.34) nm and (18.77 ± 1.23) nm with zeta potentials of (5.11 ± 1.03) mV and (−8.71 ± −1.23) mV and entrapment efficiencies of (94.1 ± 2.37)% and (95.6 ± 2.43)%, respectively. In vitro release studies indicated that the TET-CNP and TET-NP retained the drug entity better than tetrandrine ophthalmic solutions (TET-SOL). In the pharmacokinetics studies, the AUC values of TET-CNP and TET-NP were 1.96-fold and 2.00-fold higher than that of TET-SOL ( p < 0.05); the Cmax values of TET-CNP and TET-NP were 2.45-fold and 2.53-fold higher than that of the TET-SOL (p < 0.05), respectively. Cytotoxicity study showed that TET-CNP and TET-NP had no significant toxicity at low concentrations. Flow cytometry studies and confocal microscopy analysis demonstrated that calcein labeled NP (CA-NP) uptake by SRA 01/04 cells was much higher than those of calcein labeled CNP (CA-CNP) and calcein solution (CA-SOL).